Robust stability of milling operations based on pseudospectral approach. (February 2020) - Hajdu, David; Borgioli, Francesco; Michiels, Wim; Insperger, Tamas; Stepan, Gabor
Abstract: The prediction of chatter-free machining parameters is not reliable for industrial applications without guaranteed robustness against modeling uncertainties. Measurement inaccuracies, fitting uncertainties, simplifications and modeling errors typically lead to a mismatch between the mathematical model and the real physical system. This paper presents the robust stability analysis of milling operations based on a pseudospectral approach to take into account the effect of bounded parametric uncertainties both in the cutting coefficients and in the modal parameters. In order to make the predictions more accurate, the operational modal analysis of the spindle during rotation was conducted. The natural frequencies and damping ratios of the dominant vibration modes were identified from the impact tests of the rotating tool at different spindle speeds. The uncertainties of the fitted parameters were included in the computation of the pseudospectral radius of the monodromy operator of the time-periodic system. The solver is tested in a case study and experimental chatter tests are also included for demonstration purposes. Graphical abstract: Highlights: A robust pseudospectral method is presented for milling operations considering uncertainties in both modal parameters and cutting coefficients. The stability analysis is based on a collocation method using Chebyshev polynomials. Modal parameters of the rotating spindle are determined by operational modal analysis. A case study with experimental chatter tests is included.